FAKTORFAKTOR YANG MEMENGARUHI EPILEPSI LOBUS TEMPORAL POTENSIAL RESISTEN OBAT - Andini Aswar, Fitri Octaviana, Astri Budikayanti , Joedo Prihartono (Neurona Majalah Kedokteran Neuro Sains, 2015)
INTRODUCTION THE GOAL OF MANAGEMENT PATIENTS WITH EPILEPSY IS TO ACHIEVE SEIZUREFREE IN ORDER TO REACH OPTIMAL QUALITY OF LIFE FOR PEOPLE WITH EPILEPSY CURRENTLY ANTIEPILEPTIC DRUGS AEDS ARE WIDELY USED AS A THERAPEUTIC OPTION NEVERTHELESS APPROXIMATELY 3040 OF PATIENTS ARE THOUGHT TO BE RESISTANT TO DRUG TREATMENT TEMPORAL LOBE EPILEPSY TLE IS THE MOST COMMON TYPE OF EPILEPSY WHICH IS PRONE TO BE DRUG RESISTANT FAILURE TO RESPOND TO AEDS IS A PROBLEMATIC CLINICAL ISSUE